Effect of traditional household processing techniques on phenolic compounds, antioxidants activity and γ-aminobutyric acid of cowpea (Vigna unguiculata) pods - AlGhamdi, Fatima Ali; Hassan, Amro B.; AlFaris, Nora Abdullah; AlTamimi, Jozaa Zaidan (Italian Journal of Food Science, 2023)
The influence of common home processing methods was investigated on the color characteristics, phenolic component, antioxidant activity (2,2-diphenyl-1-picrylhydrazyl [DPPH] and ferric-reducing antioxidant power [FRAP] activity) and the levels of γ-aminobutyric acid (GABA) in cowpea pods. The processing methods significantly increased the total phenolic content, total flavonoid content and the activity of antioxidant compounds (DPPH and FRAP). The GABA content sharply decreased in pods after boiling and drying treatment. However, it significantly increased after fermentation. The fermented cowpea pods displayed the highest content of phenolics, flavonoids, GABA and anthocyanin as well as antioxidant activity. Hence, these traditional domestic preparation methods could be recommended for the food industry.